2020
DOI: 10.3390/en13010271
|View full text |Cite
|
Sign up to set email alerts
|

One Convenient Method to Calculate Performance and Optimize Configuration for Annular Radiator Using Heat Transfer Unit Simulation

Abstract: In order to calculate heat transfer capacity and air-side pressure drop of an annular radiator (AR), one performance calculation method was proposed combining heat transfer unit (HTU) simulation and plate-and-fin heat exchanger (PFHX) performance calculation formulas. This method can obtain performance data with no need for meshing AR as a whole, which can be convenient and time-saving, as grid number is reduced in this way. It demonstrates the feasibility of this performance calculation method for engineering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…CFD simulation technology is adopted to obtain heat transfer capacity and air-side pressure drop of AR using ANSYS commercial software. In order to reduce the burden of simulation which will cause high computing resource requirements and large time consumption, HTU which is used in Xu et al 29 is also used in this method. As shown in Figure 1, two kinds of HTUs in total, which are HTU A and HTU B, can be obtained by dividing AR according to the symmetrical axis and the central angle of annular substrate finned area.…”
Section: Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CFD simulation technology is adopted to obtain heat transfer capacity and air-side pressure drop of AR using ANSYS commercial software. In order to reduce the burden of simulation which will cause high computing resource requirements and large time consumption, HTU which is used in Xu et al 29 is also used in this method. As shown in Figure 1, two kinds of HTUs in total, which are HTU A and HTU B, can be obtained by dividing AR according to the symmetrical axis and the central angle of annular substrate finned area.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…The method of performance analysis used in most of the previous researches is emulating a heat exchanger as a whole directly, which is not realistic for AR simulation as the mesh number will be extremely huge in this way. In the research of Xu et al, 29 one kind of heat transfer unit (HTU) of AR was proposed and one theoretical arithmetic method combining with HTU CFD simulation was adopted to predict heat transfer capacity and air-side pressure drop of AR. In addition, number of fins in circumferential direction (NFCD) and fin height (FH) of AR were optimized to increase the heat transfer capacity and decrease the air-side pressure drop by NSGA-II.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of optimization has infinite amount of good solution if it would be on the Pareto front [19]. For multi objective optimization Pareto diagram is a highly preferred option [19][20][21][22][23][24].…”
Section: Pareto-vector Length Optimizationmentioning
confidence: 99%
“…The applicability of finned tubes to a large condenser system with a bundle layout was verified. Xu et al [9] computed the heat transfer capacity and air-side pressure drop of an annular radiator (AR) using a combined heat transfer unit (HTU) simulation and plate-and-fin heat exchanger (PFHX) performance calculation formulas. Results indicated that their optimization method could provide significant guidance for AR design.…”
Section: Introductionmentioning
confidence: 99%